TERRITORIAL ENVIRONMENTAL PROBLEMS MACROREGIONAL ANALYSIS CENTER AND BUCURESTI - ILFOV REGIONS - Rosu, Elisabeta (Economics of Agriculture, 2012)
The environmental problems are phenomena determined by essential modifications that are produced in nature under mans influence. Initially the environmental problems have a local origin, yet they affect large areas and finally become regional or global problems.